Analisis Penulisan Email dalam Bahasa Jepang pada Mahasiswa Semester 117 Mata Kuliah Tegami no Kakikata - Yuniarsih; Putra, Joe Ariska (Universitas Airlangga, 2023)
Writing business emails in Japanese has some challenges for second language learners. This can be seen from the mistakes made by students on the exam results of the Tegami no Kakikata course in the Pendidikan Bahasa Jepang study program at Universitas Negeri Jakarta. This research utilized qualitative methods with documentary techniques to identify errors in Japanese business email writing. The findings revealed various language errors within Japanese business emails. A major finding was the prevalence of Sonota (miscellaneous) errors, accounting for 58.5% of the total errors. This category indicates diverse errors that cannot be specifically classified into other categories. Furthermore, errors categorized under Datsuraku (omission of sentence elements) ranked second, totaling 32 errors or 20%. Additionally, Gokeishiki (word formation errors) represented 26 errors or 16%. Following these were Fuka (addition of sentence elements) with 7 errors (4.5%), Ichi (misplacement) with 2 errors (1%), and Kondo (exchange errors) which had no recorded errors. From the predominantly Sonota errors, the order of prevalence of errors in Japanese business email can be arranged from most common to least common. The highest error category was Kata/kalimat kurang tepat (inaccurate phrases/sentences) at 27%, followed by Pemahaman instruksi soal (understanding instructional questions) at 17%, Penulisan kenmei (件名) (kenmei writing) and Penggunaan 様 dan さん (usage of 様 dan さん) (16% each). Subsequently, Konsep uchi dan soto (uchi and soto concept) and Penulisan kanji (kanji writing) had 10% each, Interferensi bahasa Indonesia (interference of Indonesian language) had 4%, and Pleonasme had 2%, depicting fewer errors. The analysis indicates common errors in Japanese business emails are associated with inaccurate phrases/sentences, while less common errors are related to Pleonasme.